PENERAPAN PRINSIP PEMBELAJARAN ANDRAGOGI DALAM Q.S AL-KAHFI AYAT 60-82 : STUDI DI PROGRAM STUDI MAGISTER PAI UIN SMH BANTEN - MADJID NURFARUQI; HUNAINAH HUNAINAH; HANNANAH HANNANAH (CENDEKIA: Jurnal Ilmu Pengetahuan, 2022)
The purpose of this research is to explain: 1) The principles of andragogy learning in Q.S al-Kahfi verses 60-82, 2) The principles of andragogy learning in the Islamic Religious Education Masters Study Program at UIN Sultan Maulana Hasanuddin Banten, 3). Application of andragogy learning principles in the Islamic Religious Education Masters Study Program at UIN Sultan Maulana Hasanuddin Banten and 4) Supporting and inhibiting factors in the application of andragogy learning principles in the PAI Masters Study Program at UIN Sultan Maulana Hasanuddin Banten. In this research, the approach taken is qualitative, namely research that produces data on the study of Al-Quran texts from three tafisr books (Ibnu Katsir, al-Mishbah and Jalalain) as well as descriptive in the form of written or spoken words from observable people in the form of interviews with seven respondents. The results of this study, 1) The principles of andragogy learning in surah al-Kahf verses 60-82 namely, self-motivation (verses 60-61), constructivism (63-64), learning contracts (verses 65-70), dialogic (verses 71- 78) and mastery learning (verses 79-82). 2) The principles of andragogy learning in the PAI Masters Study Program at UIN Sultan Maulana Hasanuddin Banten from the results of interviews include attention, motivation, activeness, direct involvement, interest, experience, dialogic, democratic, egalitarian, creative and analytical. 3) The application of the learning principle of andragogy in Q.S al-Kahf verses 60-82 in the Islamic Religious Education Masters Study Program at UIN Sultan Maulana Hasanuddin Banten is the principle of motivation and discussion, this principle is also applied by the lecturers in learning. 4) Supporting factors, namely the existence of sophisticated media such as Google Meet, Google Scholar, Google Classroom, Online Library, Zoom Meet and Voice Notes. In addition to sophisticated media, there must be infrastructure that can support learning as well as strategies, media, methods and evaluation of learning so that it becomes good learning. Inhibiting factors, students have limited time. Another inhibiting factor is a feeling of laziness to read. Tools and materials such as laptops and cellphones must be supported. ABSTRAKTujuan penelitan ini untuk menjelaskan: 1) Prinsip pembelajaran andragogi dalam Q.S al-kahfi ayat 60-82, 2) Prinsip pembelajaran andragogy di Program Studi Magister Pendidikan Agama Islam UIN Sultan Maulana Hasanuddin Banten,  3). Penerapan prinsip pembelajaran andragogy di Program Studi Magister Pendidikan Agama Islam UIN Sultan Maulana Hasanuddin Banten dan  4) Faktor pendukung dan penghambat dalam penerapan prinsip pembelajaran andragogy di Program Studi Magister PAI UIN Sultan Maulana Hasanuddin Banten. Pada penelitian ini pendekatan yang ditempuh adalah kualitatif, yaitu penelitan yang menghasilkan data kajian teks al-Quran dari tiga kitab tafisr (Ibnu Katsir, al-Mishbah dan Jalalain) serta deskriptif berupa kata-kata tertulis atau lisan dari orang-orang yang dapat diamati berupa wawancara dengan tujuh  responden. Hasil penelitian ini, 1) Prinsip pembelajaran andragogy dalam surat al-kahfi ayat 60-82 yaitu, self motivation (ayat 60-61), konstrutivisme (63-64), learning contract (ayat 65-70),  dialogis (ayat 71-78) serta mastery learning (ayat 79-82). 2) Prinsip pembelajaran andragogy di Program Studi Magister PAI UIN Sultan Maulana Hasanuddin Banten dari hasil wawancara diantaranya, perhatian, motivasi, keaktifan, keterlibatan langsung, minat, pengalaman, dialogis, demokratis, egaliter, kreatif dan analitis. 3) Penerapan prinsip pembelajaran andragogy dalam Q.S al-Kahfi ayat 60-82 di Program Studi Magister Pendidikan Agama Islam UIN Sultan Maulana Hasanuddin Banten adalah prinsip motivasi dan diskusi, prinsip ini diterapkan juga oleh para dosen dalam pembelajaran. 4) Faktor pendukung, yaitu dengan adanya media yang canggih seperti google meet, goole cendekia, google classroom, perpustakaan online, zoom meet dan voice note. Selain media yang canggih harus adanya sarana prasarana yang mampu menunjang dalam pembelajaran serta strategi, media, metode dan evaluasi pembelajaran agar menjadi pembelajaran yang baik. Faktor penghambat, mahasisiwa memilki keterbatasan waktu, Faktor lain yang menghambat adalah rasa malas membaca. Alat dan bahan seperti laptop dan handphond harus support.